Effectiveness of a Transfer Function Method for Evaluating Vibration Isolation Performance of Gloves When Used with Chipping Hammers - Dong, R.G.; McDowell, T.W.; Welcome, D.E.; Rakheja, S.; Caporali, S. A.; Schopper, A. W. (Journal of Low Frequency Noise, Vibration and Active Control, 2002)
Anti-vibration gloves have been used as personal protective equipment to reduce the exposure intensity of hand-transmitted vibration. Although a method based upon the measured transfer function has been recently proposed to predict the tool-specific anti-vibration performance of these gloves, its validity for real tool applications has not been sufficiently evaluated. In this study, the effectiveness of the proposed prediction method was examined using two typical vibration-attenuation gloves when used in conjunction with two different pneumatic chipping hammers. Six adult male subjects were employed in the experiments involving measurement of gloves transmissibility while operating the selected tools. A comparison of the measured vibration transmissibility with the predicted values revealed that the transfer function method provides a reasonably good prediction of the vibration isolation performance of the gloves. The differences between the predicted and measured mean values of the weighted transmissibility were surprisingly small. It is concluded that the transfer function method can serve as an effective and convenient approach for estimating the effectiveness of anti-vibration gloves when used with pneumatic chipping hammers. A pneumatic chipping hammer is considered to represent a critical case for the evaluation of the method because they are typical percussive tools that generate impact vibration. It is thus anticipated that the transfer function method may also be widely employed to predict anti-vibration glove performance when used with many other vibrating tools.